Smurf2 up-regulation activates telomere-dependent senescence - Zhang, Hong (Cold Spring Harbor Laboratory Press, 2004)
Progressive telomere shortening activates replicative senescence, which prevents somatic cells from being propagated indefinitely in culture. The limitation of proliferative capacity imposed by replicative senescence is thought to contribute to both organismal aging and the prevention of tumor development. Here we report that up-regulation of Smurf2, an E3 ubiquitin ligase previously implicated in TGF-β signaling, is a specific consequence of telomere attrition in human fibroblasts and that such up-regulation is sufficient to produce the senescence phenotype. Adventitious production of the Smurf2 protein in early passage fibroblasts at the same physiological level observed during telomere-mediated senescence resulted in proliferative arrest in a viable state, morphological and biochemical alterations characteristic of senescence, acquisition of senescence-specific alterations in gene expression, and reversal of cellular immortalization by telomerase. We show that the senescence-inducing actions of Smurf2 occur in the absence of detectable DNA damage or stress response, that Smurf2's effects require a novel function distinct from its E3 activity, that Smurf2 recruits the Rb and p53 pathways for senescence induction, and that while p21 is elevated by Smurf2, Smurf2-mediated senescence is independent of p21. Smurf2 is the first gene found to be both up-regulated by telomere attrition and sufficient to induce senescence.